2003
DOI: 10.1097/00005344-200305000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allopurinol Pretreatment on Free Radical Generation after Primary Coronary Angioplasty for Acute Myocardial Infarction

Abstract: Allopurinol, an inhibitor of xanthine oxidase, was shown to improve the regional ventricular function after coronary artery occlusion and reperfusion in animal models. The effects of oral administration of allopurinol on a transient increase in free radical generation after primary percutaneous transluminal coronary angioplasty (PTCA) in patients with acute myocardial infarction (AMI) and on their clinical outcomes were examined. Thirty-eight AMI patients undergoing primary PTCA were randomly assigned to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 37 publications
1
50
0
1
Order By: Relevance
“…105 In a study of 38 patients with acute MI, patients were randomly assigned to receive allopurinol or not before primary angioplasty. 106 Not only were slow-flow phenomena less frequent in the allopurinol group, but cardiac index measured immediately after PTCA and ejection fraction at 6 months were significantly greater in treated patients. 106 …”
Section: Clinical Studies Of Xor Inhibition In Ischemia-reperfusionmentioning
confidence: 84%
See 1 more Smart Citation
“…105 In a study of 38 patients with acute MI, patients were randomly assigned to receive allopurinol or not before primary angioplasty. 106 Not only were slow-flow phenomena less frequent in the allopurinol group, but cardiac index measured immediately after PTCA and ejection fraction at 6 months were significantly greater in treated patients. 106 …”
Section: Clinical Studies Of Xor Inhibition In Ischemia-reperfusionmentioning
confidence: 84%
“…106 Not only were slow-flow phenomena less frequent in the allopurinol group, but cardiac index measured immediately after PTCA and ejection fraction at 6 months were significantly greater in treated patients. 106 …”
Section: Clinical Studies Of Xor Inhibition In Ischemia-reperfusionmentioning
confidence: 84%
“…We have also used the noncytotoxic nicotine dose of 100 μM based on our earlier published study [4]. The 8.5-μM dose of allopurinol used in our study was calculated based on the plasma levels obtained in a study of acute myocardial infarction [39].…”
Section: Discussionmentioning
confidence: 99%
“…The role of oxidative stress secondary to XO in ischemia-reperfusion injury has also been addressed in several clinical trials in humans. Guan et al [27] found that patients receiving allopurinol prior to reperfusion during coronary angioplasty had improved left ventricular function that was significant 6 months after the procedure.…”
Section: Ischemia Reperfusionmentioning
confidence: 99%